Zagadnienie reglamentacji handlu i produkcji broni, amunicji i materiału wojennego w organach Ligi Narodów - Gilas, Janusz (Acta Universitatis Lodziensis. Folia Historica, 1983)
The article deals with one of two essential trends in activity of ihe League of Nations in the field of disarmament, and namely with attempts made to control trade and production of weapons, ammunition and war material. Achievements of the League of Nations in this area were unquestionable. In line with art. 8 § 5 and 6 and art. 23 item d of the Pact of the League of Nations a convention was signed concerning international trade in weapons, ammunition and war materials on 17th June 1925 replacing resolutions of the treaty of Saint-Germain from 10th September 1919. Moreover, there was introduced a principle of disclosing information concerning armaments rate in military, navy and air-force programmes as well as the situation in industries which might be utilized for military purposes within the framework, of a special military yearly publication of the League of Nations. Apart from that, the problems of private production of weapons, ammunition and war material received broader consideration.